Social inclusion and territorial development through social innovation: experience of participative finance - EL MAAROUFI , Ismail; HARROUSSI , Baha Eddine; DRISSI , Zineb (Revue Internationale des Sciences de Gestion, 2024)
Participative banks are a kind of social innovation because they provide the territory with an alternative economy aimed at strengthening links between economic actors sharing a territory. Alternative finance is a branch of the ethical and social economy that helps to eliminate marginalization and social inequalities towards socially ethical integration and inclusion. The intention to pursue guidelines for social innovation comes from the fact of attributing to the territory new management policy in order to maximize survival in this territory. Indeed, the introduction of alternative participative finance is a component of social innovation that gives the social and territorial economy a new breathlessness allowing a comprehensive integration and inclusion of all actors and agents economic sharing the same territory. The objective of this research is to demonstrate the potential impact of participatory finance on territorial development in Morocco. It aims to explore and justify the originality of the link between participatory finance and social innovation, showing how this approach can be logical, rational, and applicable in reality. Additionally, the goal is to highlight Morocco’s role as a pioneer in this field and its intention to share this experience with other African countries to offer a social and ethical alternative.